Factors Affecting Employee’s Performance Among Administrators In Malaysian Public Universities: The Mediating Role Of Employee Agility - Nadzim, Siti Zaleha Ahmad (2024)
Industrial Revolution 4.0 (IR 4.0) demands changes in the use of digital technology that also affects the service sector and the education sector. Administrators need to be agile in facing this era of change and show good work performance along with the circulation of digital technology to ensure that they can provide the best service to customers and stakeholders. However, previous research on the performance of administrators in the era of IR 4.0 especially in Malaysian public universities has received little attention. The agility of administrators is necessary to improve their performance. For that, the purpose of this research is to study the influence of factors (digital competence, employee empowerment, teamwork and talent management) on employee agility and how employee agility can mediate the relationship between factors (digital competence, employee empowerment, work teamwork and talent management) and employee performance. A total of 310 data were obtained from administrators in Malaysian public universities through a survey form that was designed and pre-tested by administrators at Malaysian public universities and academic experts. Data was analysed using Partial Least Square-Structural Equation Modelling (SEM-PLS) through Smart PLS4 software. The results of the study show that digital competence, employee empowerment, and teamwork have a positive and significant relationship with employee agility among administrators in Malaysian public universities. It also found that employee agility has a positive and significant relationship with employee performance.